(untitled) (Research, Society and Development, 2020)
This study aimed to characterize publications on the theme of business games, for this purpose, a survey was conducted on the Spell platform covering the entire period available. The study is characterized as descriptive research with qualitative-quantitative approach. After selecting the articles, content analysis of all abstracts of publications was performed using the IRaMuTeQ software. In this study, for the analysis data, we use: the descending hierarchical classification (CHD), similarity analyzes and word cloud. This work is relevant because identifies the main terms that are linked to the theme of business games. Such information is very important, as it makes it possible to visualize the different themes to which the theme is linked. The platform’s search engine returned 66 articles, 36 of which were discarded by the exclusion criteria. Thus, the abstracts of 30 articles were analyzed, 19 with a theoretical-practical focus and 11 with a theoretical focus. The study made it possible to verify that through the business game it is possible to train the participants to make more assertive decisions. This study also shows that the IRaMuTeQ software represents an important tool for this type of study, considering that it revealed, from the collected material, such vocabulary and several others during the 7 classes obtained through the CHD method.